The Efficacy and Microstructure Effects of Insider Trading Regulations - Gilbert, Aaron (Auckland University of Technology, 2007)
The competition for external capital amongst small and developing financial markets has resulted in a growing awareness of the importance of investor protection laws if markets are to be competitive. One particularly important aspect of such laws is the need to control the behaviour of insiders. Insider trading, widely perceived as trading by investors who have an unfair advantage by virtue of access to confidential information, represents a significant threat to market confidence and investors' willingness to invest in the market. For small markets therefore, not controlling such behaviour represents a significant cost in terms of the development of the market and the economy as a whole. However, while insider trading can do significant harm to the market, it also has the potential to be beneficial to the market as a signal of incorrectly priced information. The question becomes therefore how best to balance the advantages and disadvantages of insider trading. Most markets have relied on regulations to control insiders, however, little research has been done to establish if this is effective.This thesis seeks to provide additional evidence with respect to the role of regulation in controlling insider trading. The issue is explored within the context of the New Zealand market where recent legislation, the Securities Market Amendment Act 2002, offers a prime opportunity to seek further understanding on the issue. In particular, four studies focussed on the role of regulation with respect to insider trading are undertaken within this thesis. In the first the impact of the law change on the profitability and informational base of insiders is examined. A significant decline in profitability is observed in addition to evidence of a change in the informational basis of insiders' trades from knowledge of upcoming announcements to short-term market mispricing. The impact of the new law on four aspects of the market is then examined. A significant increase in liquidity is found following the introduction of the new law, as well as significant reductions in the cost of equity, bid-ask spread and return volatility. The law therefore appears to have improved these aspects of the market. The bid-ask spreads were then examined in more depth by observing the impact of the laws on the cost of informed trading. Strong evidence of a decline in the cost of informed trading was observed, along with significant decreases in the proportion of the spread composed of information asymmetry costs. The declines were largest for those firms most prone to insider trading.Lastly, the elements of an effective insider trading regime were investigated by examining the impact of various legal variables on the cost of informed trading and the total spread. The results indicated that stronger laws have resulted in lower spreads and less informed trading costs, and that effective regimes should prevent insiders passing on their information, should rely on financial penalties over criminal sanctions, and should be both enforceable and policed by a strong public regulator. Overall this thesis finds strong evidence that insider trading laws can be effective in controlling the behaviour of insiders, and that well drafted statutory regulations can be of significant benefit to the market.
Keywords: Securities Market Amendment Act 2002; Insider traders; Securities; New Zealand